Anti-Slosh Baffle Performance In Horizontal Cylindrical Separator Tank - Liew, Shan Kun (Universiti Sains Malaysia, 2017)
In oil extraction process, baffle is employed in the horizontal cylindrical separator tank to dampen the sloshing dynamics of the fluids mixture. Different baffle configurations affect the efficiency of the separation process and anti-sloshing performance. Simulation of different baffle configurations was conducted using ANSYS Fluent software to explore the baffles performance of gate and porous types. Results from the simulation show that the porous type baffle performs better than the gate type baffle in terms of lower sloshing height and average velocity of fluid mixture across the inspection surface. Parametric study concluded that configuration 9 of porous baffle with 0.4 void fraction and 0.02 m mean particle size produces the best anti-sloshing performance.